Microstructure and characterization of (Ti, V, Nb, Ta)(C, N) high-entropy ceramic. Issue 24 (15th December 2021) - Han, X.Q.; Lin, N.; Li, A.Q.; Li, J.Q.; Wu, Z.G.; Wang, Z.Y.; He, Y.H.; Kang, X.Y.; Ma, C.
Abstract: (Ti0.25 V0.25 Nb0.25 Ta0.25 )(C1-x Nx ) high-entropy ceramics with various N contents (x = 0, 0.1, 0.2, 0.3) were successfully produced by spark plasma sintering to investigate the influence of N element on their microstructure and properties. The mixed carbide and nitride powders were sintered to form a single-phase face-centered cubic structure ceramic with a uniform composition at 2100 °C for 10 min. The introduction of slight nitrides in high-entropy ceramics refined the grain size and enhanced the hardness of ceramics. The (Ti0.25 V0.25 Nb0.25 Ta0.25 ) (C0.8 N0.2 ) ceramic demonstrated a fine grain size of 5.29 μm, a high relative density of 96.7% and an excellent hardness values of 20.6 GPa at 9.8 N and 29.3 GPa at 50 mN. With increasing contents of nitrides, the wear resistance and thermal conductivity of high-entropy ceramics increased firstly and then decreased. The ceramic with 30 at.% nitrides showed a relatively low thermal conductivity of 11.27 W m −1 K −1 at room temperature. The high-entropy carbonitride ceramics had a potential application in high temperature structure parts and machining tools.